Problematics of Religious Character Building and Discipline in Students of SMA Kartika 1-2 Medan - Yunita Yunita (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
Abstract: Problematics of Religious Character Building and Discipline in Students of SMA Kartika 1-2 Medan. This research is motivated by the many behaviors of students in class XI of SMA Kartika 1-2 Medan that do not reflect a religious and disciplined character. This research aims to find out what the problems in the formation of religious and disciplinary character and what are the inhibiting factors in the formation of the religious and disciplinary character of class XI students of SMA Kartika 1-2 Medan, This type of research uses qualitative methods with a descriptive approach, using interview techniques, observation, and documentation. The results showed that: Problematics of Religious Character Building and Discipline of class XI SMA Kartika 1-2 Medan, namely: students do not obey the rules, lack of cooperation between teachers and parents, the methods used by teachers are not optimal, and the factors that become obstacles in the formation of religious character and discipline of class XI students are: internal factors that come from within the students themselves, namely: lack of willingness from within students, and students who are difficult to manage and external factors, namely: Lack of attention from parents, environment and association of students who are less supportive and the negative impact of the internet and online games.Abstrak: Problematika Pembentukan Karakter Religius dan Disiplin pada Siswa SMA Kartika 1-2 Medan. Penelitian ini dilatarbelakangi oleh banyaknya perilaku siswa kelas XI SMA Kartika 1-2 Medan yang tidak mencerminkan karakter religius dan disiplin. Penelitian ini bertujuan untuk mengetahui apa saja yang menjadi permasalahan dalam pembentukan karakter religius dan disiplin dan apa saja yang menjadi faktor penghambat dalam pembentukan karakter religius dan disiplin siswa kelas XI SMA Kartika 1-2 Medan, Jenis penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif, dengan menggunakan teknik wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa: Problematika Pembentukan Karakter Religius dan Disiplin siswa kelas XI SMA Kartika 1-2 Medan, yaitu: siswa tidak mentaati peraturan, kurangnya kerja sama antara guru dengan orang tua, metode yang digunakan guru kurang maksimal, dan faktor-faktor yang menjadi kendala dalam pembentukan karakter religius dan disiplin siswa kelas XI yaitu: faktor internal yang berasal dari dalam diri siswa itu sendiri yaitu: kurangnya kemauan dari dalam diri siswa, dan siswa yang sulit diatur dan faktor eksternal yaitu: Kurangnya perhatian dari orang tua, lingkungan dan pergaulan siswa yang kurang mendukung serta dampak negatif dari internet dan game online.